Cyto-morphological abnormalities and cell membrane integrity of frozen-thawed spermatozoa of Frieswal bulls and their relationship with fertility - MANDAL, D K; TYAGI, S; KUMAR, M; MATHUR, A K (The Indian Journal of Animal Reproduction, 2007)
Frozen thawed semen of 5 adult Frieswal bulls were evaluated for motility (%), abnormal sperm cytomorphology and subjected to hypo-osmotic swelling (HOS) test to assess membrane integrity of the spermatozoa. Fertility rate of these bulls was assessed on a field based progeny testing programme. The over all post thaw motility and total abnormal spermatozoa in the thawed semen was 42.56±1.29 and 14.26±0.04 %, respectively. The mean percentage ofabnormal ities in the head, mid piece and tail region of the spermatozoa was 6.19±0.67, 4.37±0.35 and 3.70±0.35, respectively. The over all response of spermatozoa in HOS solution was 33.67±1.25 % with a range of 30.50± 1.00 to 35.88±3.14 % among the bulls, and did not differ (P<0.05). Fertility rate ofbulls showed negative c01Telation (P<0.05) with sperm abnormality per cent (r= -0.93). HOS-positive sperm showed positive (P<0.0 I) relationship (r =0.98) with fertility rate. It was concluded that assessment of sperm morphological abnormality and membrane integrity (HOS-test) could be useful in evaluating fe rt ility ofFrieswal bulls under field conditions.